Analysis of Condom Use Among Female Sex Workers as an Effort to Prevent HIV/AIDS in Kendari City: Cross Sectional Study - Adius Kusnan; Nur I. Purnamasari; Nisa M. Arman; La O. Alifariki (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2022)
Background: One of the populations at high risk of HIV/AIDS is Female Sex Workers (FSW) due to unsafe sex behavior, namely changing partners. The use of condoms is one of the initiatives to prevent the transmission of HIV/AIDS, and its use can be influenced by various variables. Purpose: This research intends to comprehend what factors relate to condom use to female sex workers as a HIV/AIDS prevention effort. Methods: This cross sectional study is an observational analytic study conducted in Kendari City with a sample of 65 people according to the inclusion and exclusion criteria selected using purposive sampling, data analysis using the Pearson chi-square test. Results: According to the results of the study, it was found that most of the FSW were 20-30 years old (76.9%), from Kendari (73.8%), last education was high school (64.6%), marital status was unmarried (75.4%), had good knowledge regarding HIV/AIDS and condoms (58.5%), had positive attitudes about condom use (66.2%), had exposure to information about condoms to prevent HIV/AIDS (95.4%) and always used a condom (55.4%). The results of this study indicated that there was a relationship between knowledge (p-value = 0.012) and attitude (p-value = 0.027) of condom use in FSW. There was no correlation between information expose (p-value=0.084) with condom use in FSW. Conclusion: FSW who have less knowledge and negative attitudes tend to have implications for decreasing condom use.